Intelligent negotiation- the negotiation practice and principles in health organizations daily activities - Teles Rosso, Daniela (O Mundo da Saúde, 2006)
This article aims to discuss Negotiation practices and principles in hospitals and other health institutions. The discussion has as guidelines Intelligent Strategies and Uses that a professional from this area (doctors, nurses, administrators, etc.) can and must use in interdepartamental or interfunctional negotiations in the hospital web complex. Remembering that Socrates philosophical notion “Know thyself” is always the principle of everything.